Prevalence, drug resistance, and genotypic diversity of the RDRio subfamily of Mycobacterium tuberculosis in Ecuador: a retrospective analysis for years 2012–2016 - Castro-Rodriguez, Bernardo; Franco-Sotomayor, Greta; Benitez-Medina, Jose Manuel; Cardenas-Franco, Greta; Jiménez-Pizarro, Natalia; Cardenas-Franco, Camilo; Aguirre-Martinez, Juan Luis; Orlando, Solon Alberto; Hermoso de Mendoza, Javier; Garcia-Bereguiain, Miguel Angel (Frontiers in Public Health, 2024)
A major sublineage within the Mycobacterium tuberculosis (MTB) LAM family characterized by a new in-frame fusion gene Rv3346c/55c was discovered in Rio de Janeiro (Brazil) in 2007, called RD Rio , associated to drug resistance. The few studies about prevalence of MTB RD Rio strains in Latin America reported values ranging from 3% in Chile to 69.8% in Venezuela, although no information is available for countries like Ecuador. A total of 814 MTB isolates from years 2012 to 2016 were screened by multiplex PCR for RD Rio identification, followed by 24-loci MIRU-VNTR and spoligotyping. A total number of 17 MTB RD Rio strains were identified, representing an overall prevalence of 2.09% among MTB strains in Ecuador. While 10.9% of the MTB isolates included in the study were multidrug resistance (MDR), 29.4% (5/17) of the RD Rio strains were MDR. This is the first report of the prevalence of MTB RD Rio in Ecuador, where a strong association with MDR was found, but also a very low prevalence compared to other countries in Latin America.It is important to improve molecular epidemiology tools as a part of MTB surveillance programs in Latin America to track the transmission of potentially dangerous MTB stains associated to MDR TB like MTB RD Rio .